Antimicrobial stewardship in pediatrics: focusing on the challenges clinicians face - Bowes, Jennifer (BMC Pediatr, 2014)
BACKGROUND: Antimicrobial use is very common in hospitalized children. An assessment of clinician’s prevailing knowledge and clinical approach to prescribing antimicrobials is helpful in order to develop the best strategies for successful stewardship programs. The objectives of the study were to determine fundamental knowledge of principles, approach to antimicrobial use through the clinical vignettes and to identify perceived challenges in decreasing antimicrobial use. METHODS: A questionnaire was developed by subject matter experts and pretested to ensure validity. Using a cross-sectional prospective design, the questionnaire was completed anonymously by staff and trainee physicians at a single tertiary care pediatric hospital between late November 2011 and February 2012. RESULTS: Of 159 eligible physicians, 86 (54.1%) responded, of which 77 (46 staff and 31 trainees) reported regularly prescribing antimicrobials. The majority of physicians had modest knowledge of factors that would increase risk of resistance however, less than 20% had correct knowledge of local resistance patterns for common bacteria. Almost half of physicians correctly answered the clinical vignettes. Over half of trainees and one third of staff relied most on online manuals for information regarding antimicrobials to assist prescription decision-making. Overall, physicians perceived that discontinuing empiric antimicrobials was the most difficult to achieve to decrease antibiotic use. CONCLUSIONS: Our results highlight several challenges that pediatric practioners face with respect to knowledge and approach to antimicrobial prescribing. Pediatric stewardship programs could in this setting focus on discontinuing antimicrobials appropriately and promoting local antibiograms in the proper clinical setting to decrease overall use of antimicrobials.